(untitled) (Bangladesh Journal of Agricultural Research, 2007)
Yield response factors at vegetative and yield formation stages of wheat (var. Protiva) were determined in clay loam soil of Rajshahi and in silty clay loam soil of Joydebpur. The value of the factor at vegetative stage was the same (0.18) in both the locations. But those at yield formation stage were 0.46 in Rajshahi and 0.45 in Joydebpur. Using these values in conjunction with the potential yield and stage wise evapotranspiration of wheat, the crop production functions were obtained as: Yv = 3.36+0.009 ETav; 50 mm ? ETav ? 83 mm and Yyf = 2.22 + 0.0214 ETayf; 53 mm ? ETayf ? 88 mm in Rajshahi and Yv = 2.76 +0.0075 ETav; 48 ? ETav ? 80 and Yyf = 1.82 + 0.02 ETyf; 47 ? ETayf ? 78 in Joydebpur Where, Yv is the expected yield (t/ha) of wheat for water deficit in vegetative stage, Yyf is the expected yield (t/ha) for water deficit in yield formation stage, ETav and ETayf are the crop evapotranspirations (mm) at vegetative and yield formation stages, respectively. All other stages except that received deficit irrigation were irrigated a per stage requirement. Bangladesh J. Agril. Res. 32(2) 2007: 171-182